APPLICATION OF TOPSIS METHOD FOR DETERMINATION OF ENGLISH COURSE INSTITUTION - Sukamto Sukamto; Riki Ario Nugroho; Bayu Kharesma (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: English course institutions are one of the most sought after non-formal education places to learn and improve English language skills, especially to be able to master the TOEFL well. To choose a suitable course institution, that is by visiting the respective course places. Of course, things like this take a lot of time, effort, and money. For this reason, a decision support system is needed that can provide recommendations for the best course institutions using the TOPSIS method. The data used are 18 alternatives with criteria including course fees, number of facilities, length of study hours, instructor's TOEFL, and distance from the course. The calculation results provide a recommendation that the alternative A Class IBT is the best English course institution. Keywords: English Course; Decision Support System; TOPSIS  Abstrak:. Lembaga kursus bahasa inggris merupakan salah satu tempat pendidikan nonformal yang saat ini banyak dicari untuk mempelajari dan meningkatkan kemampuan bahasa inggris khususnya untuk dapat menguasai TOEFL dengan baik. Untuk memilih lembaga kursus yang cocok yaitu dengan mendatangi ke tempat kursus masing-masing. Tentunya hal seperti ini banyak waktu, tenaga, dan biaya yang diperlukan. Untuk itu diperlukan suatu sistem pendukung           keputusan yang dapat memberikan rekomendasi lembaga kursus yang terbaik menggunakan metode TOPSIS. Data yang digunakan adalah 18 alternatif dengan kriteria antara lain uang        kursus, jumlah fasilitas, lama jam belajar, TOEFL instruktur, dan jarak tempat kursus. Hasil    perhitungan memberikan rekomendasi bahwa alternatif A Class IBT merupakan lembaga kursus bahasa Inggris yang terbaik. Kata kunci: Kursus Bahasa Inggris; Sistem Pendukung Keputusan; TOPSIS